Pairwise host preference of the maize weevil, Sitophilus zeamais among several Indonesian cereal grains - M. Bayu Mario; Muhammad Taufik; Asra Asra; Ahmad Komaini; Idul Anshar; Paridah Paridah; Wardani Syahrani; Laila Al Atsariyah; Bhintang Maharani; Ravindra Chandra Joshi; Lekhnath Kafle; Eirene Brugman; et al. (Crop Protection, 2026)

Hydrographic structure and turbulent mixing in the Sulu Sea, Sulawesi Sea and Sangihe-Talaud Waters - Muh Firdaus; Agus Saleh Atmadipoera; Adi Purwandana; Asep Priatna; Asep Ma’mun; Muhammad Taufik (Ocean Dynamics, 2026)

Not the same plastics: Comparing abundance and composition of marine macro-litter in mangroves and beaches in Southeast Asia - Jenny Fong; Ashwini Suresh Kumar; Cheng Ling Lim; Muhammad Reza Cordova; Pham T. Hoa; Deo Florence L. Onda; Kim John N. Balboa; Norchel Corcia F. Gomez; Mochamad Riza Iskandar; Muhammad Taufik Kaisupy; Swietenia Puspa Lestari; Pham Ngoc; et al. (Journal of Environmental Management, 2026)

Coral disease diversity and observed prevalence in the Seram Laut Islands, Indonesia - Mujiyanto Mujiyanto; Andrias S. Samusamu; Ofri Johan; Reny Puspasari; Masayu Rahmia Anwar Putri; Tirtadanu Tirtadanu; Yayuk Sugianti; Karsono Wagiyo; Muhammad Taufik; Puput Fitri Rachmawati; Prihatiningsih Prihatiningsih; Rita Rachmawati; et al. (Continental Shelf Research, 2026)

Effects of coffee pulp fermentation on bioactive compounds and antioxidant activity of coffee pulp extract: a systematic review and meta-analysis - Anasya Rahmawati; Muhamad Aldi Nurdiansyah; Intan Taufik; Mia Rosmiati; Rizki Fauziah Ramadhaini; Muhammad Yusuf Abduh (Food Bioscience, 2025)

Evaluation of phenolic compounds, antioxidant activity, and sensory analysis of commercial cascara from different locations in Indonesia - Anasya Rahmawati; Diah Nofitasari; Mia Rosmiati; Intan Taufik; Muhammad Yusuf Abduh (Food and Humanity, 2025)

Divergent genetic diversity reveals contrasting demographic histories in two commercially important snappers - Achmad Zamroni; Muhammad Taufik; Tri Ernawati; Erfind Nurdin; Pratiwi Lestari; Moh Fauzi (Ecological Genetics and Genomics, 2025)

Quantitative landslide risk analysis with limited dataset by leveraging geospatial approaches in Indonesia - Dian Nuraini Melati; Astisiasari Astisiasari; Raditya Panji Umbara; Wisyanto Wisyanto; Sukristiyanti Sukristiyanti; Yukni Arifianti; Syakira Trisnafiah; Trinugroho Trinugroho; Taufik Iqbal Ramdhani; Ahmad Luthfi Hadiyanto; Argo Galih Suhadha; Diyah Krisna Yuliana; et al. (Natural Hazards, 2025)

Heavy metals contamination in Jakarta Bay sediment: geoaccumulation assessment and implication for environmental health - Idha Yulia Ikhsani; Harmesa Harmesa; Fitri Budiyanto; Hikmah Thoha; Nurul Fitriya; Muhammad Taufik Kaisupy; Singgih Prasetyo Adi Wibowo; Lestari Lestari (Marine Pollution Bulletin, 2025)

Identifying the vulnerable landforms toward climate change-related hazards on small islands using geological-geomorphological and social approaches (Kei Kecil-Tual Carbonate Islands, Southeast Maluku, Indonesia) - Indranova Suhendro; Ratih Winastuti; Sistien Adhaena Sari; Muhammad Anggri Setiawan; Eko Haryono; Taufik Waskita; Ariqonitahanif Putri Rahim; Rohima Wahyu Ningrum; Galih Aries; Wiwit Suryanto (Carbonates and Evaporites, 2025)

Resistance of several Indonesian cereal grain cultivars to the maize weevil, Sitophilus zeamais (Motschulsky) (Coleoptera: Curculionidae) - M. Bayu Mario; Muhammad Taufik; Melina Melina; Ravindra Chandra Joshi; Idul Anshar; Paridah Paridah; Ahmad Komaini; Lekhnath Kafle; Samir A.M. Abdelgaleil; Eirene Brugman; Ito Fernando (Crop Protection, 2025)

From riverbank to the sea: An initial assessment of plastic pollution along the Ciliwung River, Indonesia - Muhammad Reza Cordova; Max R. Kelly; Muhammad Hafizt; Singgih Prasetyo Adi Wibowo; Yaya Ihya Ulumuddin; Triyoni Purbonegoro; Deny Yogaswara; Muhammad Taufik Kaisupy; Riyana Subandi; Sofia Yuniar Sani; Richard C. Thompson; Susan Jobling (Marine Pollution Bulletin, 2024)

Microplastic occurrence in sub-surface waters of the Indonesian archipelago - Muhammad Reza Cordova; Mochamad Riza Iskandar; Dewi Surinati; Muhammad Taufik Kaisupy; Singgih Prasetyo Adi Wibowo; Riyana Subandi; Yaya Ihya Ulumuddin; Triyoni Purbonegoro; Deny Yogaswara; Sofia Yuniar Sani; Rachma Puspitasari; Ricky Rositasari; et al. (Frontiers in Marine Science, 2024)
The issue of plastic pollution in the marine environment is a matter of great concern. Our research presents pioneering findings on sub-surface microplastics in the Indonesian archipelagic waters. Data on microplastic presence in sub-surface water in the Indonesian Archipelagic Water is crucial for expanding our understanding of microplastic distribution from the surface to the bottom layers of the ocean, a research area that has been relatively overlooked. We discovered microplastic particles at 5 m depth below the surface through simultaneous pump method. The highest concentration of microplastics was discovered in Ambon, followed by North Java and North Sulawesi. In contrast, the lowest abundance of microplastics was detected in the Maluku Sea. These findings are consistent with prior studies establishing a relationship between human activity–as indicated by population density–and microplastic pollution. However, our results indicate that levels of microplastics in Ambon were significantly higher than those found in other sampled areas, particularly compared to North Java, which boasts the highest population density in Indonesia. This disparity is likely due to a faster seawater flushing rate and shorter water residence time in North Java relative to Ambon. The origins and pathways through which these microplastics are introduced into Indonesian archipelagic waters remain uncertain. Based on particle composition (52.73% fibers and 51.38% size <500 µm), it appears that they may result from either larger plastic items being broken down during transportation over long distances by prevailing currents from input from coastal areas or as a byproduct of local activities. Additional research is necessary to gain a comprehensive understanding of microplastic in water columns. This includes investigating the fate of microplastics and examining their impact on marine organisms within this treasured ecosystem. Moreover, it is important to develop methods for mapping the worldwide distribution of microplastics.

A Century of Ichthyoplankton Research in Indonesian waters: lessons from the past, challenges for the future - Augy Syahailatua; Muhammad Taufik; Karsono Wagiyo; Hagi Y. Sugeha; Charles P. H. Simanjuntak; Sam Wouthuyzen; Michael J. Miller; Jun Aoyama (Reviews in Fish Biology and Fisheries, 2024)

Abundance and characterization of microplastic pollution in the wildlife reserve, Ramsar site, recreational areas, and national park in northern Jakarta and Kepulauan Seribu, Indonesia - Muhammad Reza Cordova; Yaya Ihya Ulumuddin; Triyoni Purbonegoro; Rachma Puspitasari; Ricky Rositasari; Deny Yogaswara; Muhammad Taufik Kaisupy; Singgih Prasetyo Adi Wibowo; Riyana Subandi; Sofia Yuniar Sani; S. Sulistiowati; Intan Kusumastuti Nugraheni; et al. (Chemosphere, 2024)

Microplastics leaving a trace in mangrove sediments ever since they were first manufactured: A study from Indonesia mangroves - Muhammad Reza Cordova; Yaya Ihya Ulumuddin; Ali Arman Lubis; Muhammad Taufik Kaisupy; Singgih Prasetyo Adi Wibowo; Riyana Subandi; Deny Yogaswara; Triyoni Purbonegoro; Jeverson Renyaan; Doni Nurdiansah; Untung Sugiharto; Dienda Shintianata; et al. (Marine Pollution Bulletin, 2023)

Land-derived litter load to the Indian Ocean: a case study in the Cimandiri River, southern West Java, Indonesia - Muhammad Reza Cordova; Nicolas Bernier; Deny Yogaswara; Riyana Subandi; Singgih Prasetyo Adi Wibowo; Muhammad Taufik Kaisupy; Jeanette Haulussy (Environmental Monitoring and Assessment, 2023)